The Influence of Instagram Influencers’ Communication Style on Consumer Trust and Emotional Engagement in Live Streaming Shopping - Mohammad Rifky Maulana; Amalia E. Maulana (Eduvest - Journal of Universal Studies, 2026)
The rapid development of social media has given rise to new marketing strategies, one of which is live streaming shopping through platforms such as TikTok Shop. Digital influencers, especially Instagram influencers, play a key role in shaping consumer perceptions and purchasing decisions, particularly for high-involvement products such as perfume. This study aims to analyze the influence of Instagram influencer communication styles (informative, entertaining, interactive) on consumer trust and emotional engagement, and to assess the mediating role of trust and emotional engagement on sharing intention. This study uses a quantitative approach with a survey method involving 342 TikTok users who have watched perfume live streaming sessions. The data analysis technique used is Structural Equation Modeling – Partial Least Squares (SEM-PLS) with SmartPLS 4.0 software. The results show that entertaining and informative communication styles have a significant influence on trust and emotional engagement, while the interactive style has a significant influence on emotional engagement. Trust and emotional engagement are proven to mediate the relationship between communication styles and consumer behavioral intentions. This research strengthens the relevance of the SOR (Stimulus–Organism–Response) Model in the context of social commerce and provides practical contributions for brands and influencers in choosing the right communication approach based on audience segments and product characteristics.